Application of Potential and Vortex Fields to the Description of Gravitation and Electromagnetism
We propose a system of differential equations in the tensor general-covariant form whose solutions are called gravitational and charged particles. For free fields, solutions are found in the form of Newton and Coulomb potentials. For a particle that rotates with constant velocity around another particle with large mass, a solution is obtained in the form \(ω = km_2 R^3 \) if the particle is uncharged, and in the form \(ω = kε _1 ε _2 m_1 R^3 \) if it is charged., number=1, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Ivanchenko, V. M., year=2004, month=Jan., pages=31–50